2008
DOI: 10.1158/1078-0432.ccr-07-1655
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Genotypes, Haplotypes, Gender, and the Risk of Non–Small Cell Lung Cancer

Abstract: Purpose: The vascular endothelial growth factor (VEGF) is a major mediator of angiogenesis involving tumor growth and metastasis. Polymorphisms in the VEGF gene may regulate VEGF production. In this large case-control study, we investigated whether functional polymorphisms (−460C/T, +405C/G, +936C/T) in the VEGF gene are associated with the risk of non–small cell lung cancer (NSCLC). Experimental Design:VEGF genotypes and haplotypes were determined in 1,900 Caucasian patients with NSCLC and 1,45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 36 publications
5
45
1
Order By: Relevance
“…VEGF þ405G>C is located in the 5 0 -untranslated region of the VEGF gene and is in modest linkage disequilibrium with VEGF þ936C>T (D 0 ¼ 0.65À0.74); this may help explain the nonsignificant trend found with VEGF þ936C>T (34,71). Genotype-phenotype analyses suggest that the C allele VEGF þ405G>C is associated with decreased promoter activity and decreased expression of VEGF, as the C allele reduces binding of the transcription factor, MZF1, which then subsequently reduces gene expression (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF þ405G>C is located in the 5 0 -untranslated region of the VEGF gene and is in modest linkage disequilibrium with VEGF þ936C>T (D 0 ¼ 0.65À0.74); this may help explain the nonsignificant trend found with VEGF þ936C>T (34,71). Genotype-phenotype analyses suggest that the C allele VEGF þ405G>C is associated with decreased promoter activity and decreased expression of VEGF, as the C allele reduces binding of the transcription factor, MZF1, which then subsequently reduces gene expression (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic polymorphisms are considered to be molecular markers that predict the risk, progression and prognosis of various cancers (3)(4)(5)(6)(7). Indeed, single nucleotide polymorphisms (SNPs) in several genes are reported to be associated with the risk of lung cancer (8)(9)(10), for example SNPs in the caspase-3 and vascular endothelial growth factor genes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that there is a signifi cant correlation between SNPs in the VEGF, VEGFR-1, and VEGFR-2 genes and the onset and the course of sarcoidosis. As these pulmonary diseases, apart from neoplasia, 23,24 there are studies addressing the role of VEGFR in ARDS. 25 It was recently shown that genotypes and haplotypes of the VEGF gene are associated with lower VEGF plasma levels and higher mortality in patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%